Physico-chemical characteristics of the ground water table after monsoon: a case study at central Travancore in Kerala - Vishnu, Sankar S; Prince, George; Mohan, Thomas (International Journal of Environment, 2014)
Water quality plays an important role in maintaining plant and animal life. Lack of good quality drinking water and water for sanitation cause health problems. Water quality characteristics arise from a group of physical, chemical and biological factors. The dynamic balance of the aquatic system can be destroyed by human activities resulting in water pollution.Well water has traditionally considered as a safe resource of water for consumption without treatment and extensively used for individual water supply in rural and many urban areas.In this paper a preliminary analysis is done to explore the water quality of selected wells in order to correlate the effect of pollution on water quality at these locations. Water samples are collected from different regions of Vazhappally area located on central travancore of Kerala. These sites are important because people depend only on well water for drinking purpose. The samples are collected from ten locations and analyzed for chemical parameters such as pH, conductivity, salinity, turbidity, acidity, alkainity, hardness, total phosphates, dissolved oxygen, biological oxygen demand, total dissolved solids and Iron content. Samples are also analysed for coliform bacteria which cause pathogenic diseases. Remarkable differences are observed mainly in biological oxygen demand, acidity and hardness. Finally, an attempt has been done to correlate the observed chemical parameters and the waterquality standards. DOI: http://dx.doi.org/10.3126/ije.v3i2.10501 International Journal of the Environment Vol.3(2) 2014: 20-27